Effect of antecedent rainfall on pore-water pressure distribution characteristics in residual soil slopes under tropical rainfall - Rahardjo, Harianto (2011)
Characteristics of changes in pore-water pressure distribution are the main parameters associated with slope stability analysis involving unsaturated soils, which are directly affected by the flux boundary conditions (rainfall infiltration, evaporation and evapo-transpiration) at the soil–atmosphere interface. Four slopes were instrumented in two major geological formations in Singapore to provide real-time measurements of pore-water pressures and rainfall events on the slopes. The field monitoring results were analysed to characterize pore-water pressure distributions under various meteorological conditions and to study the effect of antecedent rainfall on pore-water pressure distributions in typical residual soil slopes under tropical climate. Slope stability analyses were also conducted for the best and worst pore-water pressure distributions recorded in each slope to determine the range of factor of safety for the slopes. Results indicate that, antecedent rainfall, initial pore-water pressures prior to a significant rainfall event as well as the magnitude of the rainfall event play a crucial role in the development of the worst pore-water pressure condition in a slope. The role of antecedent rainfall in the development of the worst pore-water pressure condition was found to be more significant in residual soils with low permeability as compared with that in residual soils with high permeability. Pore-water pressure variation due to rainfall was found to take place over a wide range in residual soils with higher permeability as compared to residual soils with lower permeability. The worst pore-water pressure profiles occurred when the total rainfall including the 5-day antecedent rainfall (in most cases) reached a maximum value during a wet period. The factor of safety of residual soils with low permeability was found to be unaffected by the worst pore-water pressure condition.